2008
DOI: 10.1016/j.expneurol.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular cells increase expression of ciliary neurotrophic factor following partial denervation of the rat neurohypophysis

Abstract: The expression of ciliary neurotrophic factor (CNTF) was investigated immunocytochemically during the axonal degeneration and collateral axonal sprouting response that follows partial denervation of the rat neurohypophysis. A significant increase in the number of CNTFimmunoreactive (CNTF-ir) cells was observed in the neurohypophysis of partially denervated animals compared to age-matched sham-operated controls by 5 days post-denervation, remaining elevated throughout the 30 day post denervation period. Stereom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Since the application of Bc1-XL and caspase inhibition was also found to increase the survival of the Oxt-and Avp-MCNs in the SON in organotypic culture (House et al, 2006) this lent further support for the proposal that the mechanism of axotomy-induced cell death was apoptosis (Vutskits et al, 1998). CNTF and the CNTF receptor have found to be present in the HNS system in vivo (Lo et al, 2008; Watt et al, 2006; Watt, et al, 2008) consistent with the view that this neurotrophic factor normally plays a role to sustain the MCNs in vivo .…”
Section: Introductionsupporting
confidence: 74%
“…Since the application of Bc1-XL and caspase inhibition was also found to increase the survival of the Oxt-and Avp-MCNs in the SON in organotypic culture (House et al, 2006) this lent further support for the proposal that the mechanism of axotomy-induced cell death was apoptosis (Vutskits et al, 1998). CNTF and the CNTF receptor have found to be present in the HNS system in vivo (Lo et al, 2008; Watt et al, 2006; Watt, et al, 2008) consistent with the view that this neurotrophic factor normally plays a role to sustain the MCNs in vivo .…”
Section: Introductionsupporting
confidence: 74%
“…However, the precise role of CNTF in the NL is still not known. To this point, there is evidence indicating that CNTF‐immunoreactive cells of the NL are perivascular cells that may be neuronophagic during the axonal degeneration that follows partial denervation of the 35‐day‐old rat NL (Lo, SunRhodes, & Watt, ) suggesting that CNTF may play a role in axonal degeneration, as opposed to axonal sprouting in the NL.…”
Section: Discussionmentioning
confidence: 99%
“…We previously hypothesized that CNTF plays a role in the axonal reorganization of magnocellular neurons in the SON following injury (Askvig, et al, 2012, Lo, et al, 2008, Watt, et al, 2006, Watt, et al, 2009). In support of this hypothesis we demonstrated that following axotomy CNTF and the CNTF receptor components are increased in the SON both during the period of axonal sprouting and neuronal injury (Askvig, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%